Managing a computer system and interface, performance and applications - Zeqiri, Nderim (Journal of Advanced Computer Science & Technology, 2016)
Computer system has important command under various objects. To have a stable system, there is a need to create the model and functionality in terms of management and programming. The purpose of this paper is to present computer system as a central source, and other systems management interface for external management facilities. The logic of interaction of various objects is to create structures with universal purposes. In the paper presented the functioning of the computer system with microcontrollers and especially with Arduino Uno device. Also, is analyzed the performance of computer system, and are given the perspective and other question in the context of problem-solving. So, finally is given the comparisons with other systems.